Physical Growth Retardation Among Kindergartens And Its Relation With Some Variables (Journal Of Educational and Psychological Researches, 2014)
Which children infected with physical growth retardation at childhood it will be the largest problems effecting the child and his parents together. So , at the period of early childhood, there must be a state of satisfactions of need because if they didn’t satisfied it will be very hard to be satisfied or replaced at another period because it will be busy with satisfaction of another need of new period, and even it will be satisfactions it still weak and didn’t be am efficient as the matter of if it be satisfied at the exact time      Looking at physical growth and its indicators as length and weight and making a comparison with world indicators at peer  age phases helps in specifying the state of physical growth among  children and the extent of their adjustment and creating their personalities , to ensure availability of world specifications or be near of them , the results must match with them especially in preschool phase because it is the phase of speedy building and growth . So, it is necessary to make a suitable environment and the healthy food by parents and the specialized institutions.                                    The aim of this study as following:-                                          ldentifying the relation between physical growth retardation among kindergarteners and sex , age of the child , nature of vaccines , appetite of child , marital status , academic degree of the father , academic degree of the mother , smoking of the mother , type of birth . The limits of this study:-      The sample consists of (400) children of kindergartens who had been selected randomly of (24) kindergartens of the 6th directorate with the help of their mothers to answer the items of the scale. the items of it representing the symptoms of physical growth retardation which are (field of healthy symptoms consisting of (8) items , field of motion symptoms consisting of (9) items , field of olfactory symptoms consisting (8) items , field of verbal symptoms consisting of (17) items , and the field of behavior symptoms consisting of (16) items , the field of visual bookmarks, which consists of (12) paragraph has been diagnosed by a (visual Examiner) . so , the scale consists of (70) items .   The discriminative power of the items of the scale of physical growth retardation, the relation of item with total degree of the scale , and the relation of item degree with field and validity have been         obtained .   After application of the scale on the individuals of the sample , their answer have been statistically analyzed by Qui square , person correlation coefficient , T-test of one sample , T-test of two samples , point bisereal correlation coefficient , Analysis of variance , Scheffaes test, andmuleteer regression analysis . The study reaches at the following results:- 1.There is a statistical correlation among variables of study , and (age of the child , nature of the vaccines , applied of the child , academic degree of the mother , smoking) have got statistical role in physical retardation among kindergartens (sample) as for (sex , type of birth , marital status , academic degree of the father) haven’t got  any role in the dependent variable (physical growth retardation) .    The researcher makes the following recommendations in the light of the results of the study